2006
DOI: 10.1182/blood-2005-07-2731
|View full text |Cite
|
Sign up to set email alerts
|

Failure of HIV-exposed CD4+ T cells to activate dendritic cells is reversed by restoration of CD40/CD154 interactions

Abstract: Because interactions between activated CD4 ؉ T cells and antigen-presenting cells (APCs) are crucial for optimal APC function, defective CD4 ؉ T-cell activation may contribute to APC dysregulation in HIV infection. Here, we show that CD4 ؉ T cells exposed during stimulation to noninfectious HIV having functional envelope glycoproteins failed to provide activation signals to autologous dendritic cells (DCs). Consequently, important DC functions, including production of immunoregulatory cytokines (interleukin-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…40,41,[52][53][54][55][56] In particular, pDCs produce a large amount of IFN-␣ upon exposure to infectious or noninfectious HIV. 40 Here, we showed that IFN-␤ and IFN-␥ gene expression is also increased in PBMCs in presence of HIV particles and that gp120-CD4 interaction, but not productive infection, is required for IFN gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…40,41,[52][53][54][55][56] In particular, pDCs produce a large amount of IFN-␣ upon exposure to infectious or noninfectious HIV. 40 Here, we showed that IFN-␤ and IFN-␥ gene expression is also increased in PBMCs in presence of HIV particles and that gp120-CD4 interaction, but not productive infection, is required for IFN gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that CD4 depletion strongly results in a reduction in the total numbers of all CD11cϩ dendritic cells that accumulate in the lung. Lung dendritic cells expressing CD11c most likely rely on CD4 T cells for homeostasis and proliferation, and signaling through CD40 and the lymphotoxin ␤-receptor (LT␤R) during the interaction of dendritic cells with CD4 T cells may mediate these processes (37,41). Thus, the range of cell types affected by CD4 depletion is great, but we conclude that these varying populations are not needed at all, or are not needed in great numbers, for the progressive remodeling that occurs over 4 wk of chronic allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 surface glycoprotein, gp 120, is readily shed from the cell surface due to its noncovalent association with the transmembrane Env gp41, exerting modulatory effects on bystander cells through binding to CD4, chemokine receptors or other molecules expressed by DC, such as lectins [8][9][10]. HIV-1 Env proteins were shown to functionally impair isolated primary DC [2,3,11], as well as the in vitro development and maturation of monocyte-derived DC [4][5][6][7]. HIV-2, which is associated with an attenuated form of HIV/AIDS disease as compared to HIV-1 [12][13][14][15][16][17][18][19], has a broader range of coreceptor usage [20][21][22] and elicits higher levels of neutralizing antibodies [23], suggesting that its Env has structurally distinct properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct human immunodeficiency virus (HIV) type 1 infection of these professional antigen-presenting cells, viral envelope (Env) proteins per se are able to induce a significant impairment of DC function [2][3][4][5][6][7]. The HIV-1 surface glycoprotein, gp 120, is readily shed from the cell surface due to its noncovalent association with the transmembrane Env gp41, exerting modulatory effects on bystander cells through binding to CD4, chemokine receptors or other molecules expressed by DC, such as lectins [8][9][10].…”
Section: Introductionmentioning
confidence: 99%